2017
DOI: 10.1371/journal.pone.0184943
|View full text |Cite
|
Sign up to set email alerts
|

African origin of Bradyrhizobium populations nodulating Bambara groundnut (Vigna subterranea L. Verdc) in Ghanaian and South African soils

Abstract: Flavonoids secreted by legumes play a major role as signal molecules for attracting compatible rhizobia. The aim of this study was to assess and understand the diversity of microsymbionts nodulating Bambara groundnut (Vigna subterranea L. Verdc.) landraces of different seedcoat colours using restriction fragment length polymorphism and phylogenetic analysis. Seedcoat pigmentation of landraces had effect on the diversity of microsymbionts of Bambara groundnut. Even when planted together in one hole, nodulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 51 publications
5
39
0
Order By: Relevance
“…The crop is adapted to various climatic and ecological conditions and fits well with the semi-arid climatic condition of the country. As a leguminous plant, it contributes to soil fertilization through the symbiotic fixation of atmospheric nitrogen [1] [2] [3]. Moreover, Burkina Faso is one of the main producers and exporters of bambara groundnut in West Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The crop is adapted to various climatic and ecological conditions and fits well with the semi-arid climatic condition of the country. As a leguminous plant, it contributes to soil fertilization through the symbiotic fixation of atmospheric nitrogen [1] [2] [3]. Moreover, Burkina Faso is one of the main producers and exporters of bambara groundnut in West Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic analysis of individual housekeeping genes also suggested that most of the isolates were highly aligned with B. elkanii . However, the phylogenetic positions of isolates TUTDAIAP3B, TUTDAIAP8B and TUTMCJ5B were not stable in single gene phylogenies, and this could suggest recombination, migration or horizontal gene transfer [8] , [36] .…”
Section: Discussionmentioning
confidence: 96%
“…To date, only a small number of surveys used MLSA to uncover the microsymbiont diversity in SSA. The few studies focusing on “cowpea group” rhizobia (from agricultural plants) spanned the countries of Botswana and South Africa (Steenkamp et al, 2008 ), Botswana, South Africa, and Ghana (Pule-Meulenberg et al, 2010 ), Senegal (Wade et al, 2014 ), Namibia and Angola (Grönemeyer et al, 2014 ), Ghana and South Africa (Puozaa et al, 2017 ), Mozambique (Chidebe et al, 2018 ), Kenya (Ndungu et al, 2018 ), and Ethiopia (Degefu et al, 2018 ). Their main findings were in general agreement: First, almost all detected genotypes presumably represented yet unknown species (Steenkamp et al, 2008 ; Grönemeyer et al, 2014 ; Wade et al, 2014 ; Degefu et al, 2018 ).…”
Section: Putative Bradyrhizobium Diversity To Be Umentioning
confidence: 99%
“… Maximum likelihood-based phylogeny inferred from glnII-recA sequences of SSA bradyrhizobia and species type strains. SSA isolates from agricultural plants (see legend) obtained in five African studies are represented (Steenkamp et al, 2008 ; Grönemeyer et al, 2014 ; Wade et al, 2014 ; Puozaa et al, 2017 ; Chidebe et al, 2018 ). Considerably shorter sequences were excluded, and representatives were selected for identical sequences.…”
Section: Putative Bradyrhizobium Diversity To Be Umentioning
confidence: 99%
See 1 more Smart Citation